IMPLEMENTASI JAMINAN KESEHATAN NASIONAL (JKN) OLEH BADAN PENYELENGGARA JAMINAN NASIONAL (BPJS) KESEHATAN CABANG KOTA PEKANBARU - Fahny Agnifa; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Implementation of the National Health Insurance (JKN) By The Nation-al Security Agency (BPJS) Health Branch of Pekanbaru. This study aims to determine clearly the implementation of National Health Insurance in the city of Pekanbaru which is running by the Social Security Organizing Body (BPJS) Health Branch of Pekanbaru, and to know the constraints in the implementation of JKN by BPJS Health, as well as efforts to overcome these obstacles.This study is a descriptive research. The data used are primary data and secondary data. Primary data were sourced from the officials and officers who are directly dealing with the implementation of the National Health Insurance (JKN) by BPJS Health Branch of Pekanbaru, and also the participants of the Health BPJS. Secondary data were obtained through the literature relating to the title of the thesis. Techniques of data collection was done by using observation, inter-view, and literature. After the data collected was then analyzed qualitatively. Based on the analysis that has been done can be concluded that the implementa-tion of the JKN in Pekanbaru City are fully implemented by the Health BPJS Pekanbaru City branch, assisted by stage holder, regulated in the Law of the Re-public of Indonesia Number 40 Year 2004 on National Social Security System and the Law of the Republic of Indonesia Number 24 Year 2011 About the Social Security Agency.Implementation of National Health Insurance in the city of Pekanbaru that has lasted from January 2014,runs very well because of the great support of each stage holder and also high public interest against BPJS Health. But there are still obstacles in terms of people's understanding of the procedure and also super-vision services must be made to the hospital in terms of service and explanation to the patients.Keywords: Implementation, National Health Insurance, HealthBPJS.